2023
DOI: 10.12659/ajcr.939292
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Bioprosthetic Valve Serratia marcescens Endocarditis in Intravenous Drug Users

Abstract: Case series Patients: Female, 30-year-old • Female, 30-year-old Final Diagnosis: Serratia marcescens infective endocarditis Symptoms: Chest pain • fever • leukocytosis • murmur Clinical Procedure: — Specialty: Cardiac Surgery • Cardiology • Infectious Diseases • General and Internal Medicine Objective: Unusual clinical course Background: We report 2 cases of recurrent right-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Serratia marcescens (S. marcescens) resulting in endocarditis has been described in roughly 70 case reports. A review of the literature showed only one case report of Serratia endocarditis in the prosthetic tricuspid valve due to active intravenous (IV) drug use [1].…”
Section: Introductionmentioning
confidence: 99%
“…Serratia marcescens (S. marcescens) resulting in endocarditis has been described in roughly 70 case reports. A review of the literature showed only one case report of Serratia endocarditis in the prosthetic tricuspid valve due to active intravenous (IV) drug use [1].…”
Section: Introductionmentioning
confidence: 99%